Pattern and pharmacotherapy of acute poisonings presenting to a tertiary care centre - V., Aravinda; Bedwal, Ankita; Rajarathna, Kavitha; M., Narayana Swamy (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Acute poisoning, a therapeutic emergency and one of the common causes of morbidity and mortality globally. The rate of mortality in developed countries range from 1-2%, but in India it varies between 15-30%. According to World Health Organization (WHO), globally more than three million acute poisoning cases with 2,20,000 deaths occur annually. Most of the fatalities are due to the victim not reaching the hospital in time. This study aims to evaluate the pattern of acute cases of poisoning in tertiary care hospital attached to BMCRI. Methods: Prospective, observational study based on hospital records at tertiary care hospital (twelve months). Data regarding demographic profile and treatment was collected. Data was analyzed using descriptive statistics and SPSS-24. Results: Out of a total of 810 poisoning cases, 608 were included (381 poisoning, 138 drug overdose and 89 snake bite). Organophosphorus compounds (OPC) (131/608) and Aluminium phosphide (43/608) were the commonest poisons consumed in the age group 21-30 years. Sedative-hypnotics, non-benzodiazepine antiepileptics (non BZD AEDs) and paracetamol were common drug overdose cases. Snake bite accounted for 14.6%. Conclusions: OP compounds were the most common among poisons, while sedatives-hypnotics were frequently consumed drugs, followed by Snake bite. Young adults from urban areas were the common victims with suicidal intention. This reflects the need for stringent rules regarding the availability and sale of drugs and poisonous substances.